2019
DOI: 10.1128/aem.02282-18
|View full text |Cite
|
Sign up to set email alerts
|

FlbA-Regulated Gene rpnR Is Involved in Stress Resistance and Impacts Protein Secretion when Aspergillus niger Is Grown on Xylose

Abstract: Proteins are secreted throughout the mycelium of Aspergillus niger except for the sporulating zone. A link between sporulation and repression of protein secretion was underlined by the finding that inactivation of the sporulation gene flbA results in mycelial colonies that secrete proteins throughout the colony. However, ΔflbA strain hyphae also lyse and have thinner cell walls. This pleiotropic phenotype is associated with differential expression of 36 predicted transcription factor genes, one of which, rpnR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…However, the ΔAcrpnR strain produced a significantly reduced number of conidia, while OE::AcrpnR produced a large number of conidia, indicating that AcrpnR promoted asexual sporulation. This is in contrast with the A. niger rpnR deletion strain, in which there was no difference in spore production compared with the WT [20]. The ability of AcrpnR to promote asexual development was reported for the first time in Aspergillus.…”
Section: Response To Stresscontrasting
confidence: 56%
See 4 more Smart Citations
“…However, the ΔAcrpnR strain produced a significantly reduced number of conidia, while OE::AcrpnR produced a large number of conidia, indicating that AcrpnR promoted asexual sporulation. This is in contrast with the A. niger rpnR deletion strain, in which there was no difference in spore production compared with the WT [20]. The ability of AcrpnR to promote asexual development was reported for the first time in Aspergillus.…”
Section: Response To Stresscontrasting
confidence: 56%
“…A previous study on A. niger rpnR showed that rpnR was involved in stress resistance [20]. The ΔrpnR strain decreased resistance to DTT and H 2 O 2 [20].…”
Section: Response To Stressmentioning
confidence: 89%
See 3 more Smart Citations